Merjenje toplotne izolacije gorniških čevljev - Mekjavić, Igor B. (Medicinski razgledi, 2002)
A thermal foot manikin was developed for the determination of thermal insulation (I, m2 KžW) of footwear. The thermal foot manikin calculates the thermal insulation of 10 individual segments of the foot. Each copper segment of the manikin contains an electric heater and a temperature sensor. Insulation at each segment is determined by accounting for the difference in temperature between the segmentćs surface and the surrounding medium, and the electrical power required by the segmentćs heater to maintain the segmentćs surface temperature at a pre-determined level under the prevailing conditions.The immersion insulauon values obtained using the prototype ThermalFoot Manikin were compared withČ a) measurements of thermal insulation based on the temperature difference between the segmentćs surface arzd water, and the heat flux, and b) measurements of thermal insulation based on the sarne prinicple as in (b), but with a human subject. The obtained values of thermal insulation were similar at all sites when determined with the Thermal Foot Manikin. Some regional differences were observed between the results obtained with a human-foot and the
Keywords: gorništvo; recreational mountaineering; čevlji; toplotna prevodnost; stopalo